Penerapan Digital Marketing Terhadap Penjualan UMKM Filiya Galeri - Hendrasari, Elinda; Isnata, Fatqul; Yulfajar, Amrina (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
The impact of the Covid 19 pandemic on the development of Micro, Small, and Medium Enterprises (MSMEs) has resulted in a worsening economy in Indonesia and various countries. MSMEs must find the right strategy to recover and redevelop their business. One of the strategies is digital marketing which allows MSME actors to market their products with a wider range. The problem described in this article is how to apply digital marketing to MSMEs with the UMKM Filiya Galeri sample. This study uses descriptive qualitative research with research perceptions to explain in detail the objects that are meticulous in the application of digital marketing and the method of application based on the data obtained on sales. From the results of implementing digital marketing, it is very effective and effective for reaching customers for sales. In implementing digital marketing itself, there are internal and external constraints. These obstacles include unstable internet connection, delays, and internal problems due to limited human resources and raw material suppliers.